The Strengthening of Guardian Institutions in Nanggroe Aceh During the Autonomy Era - Muhammad Ridwansyah; Asron Orsantinutsakul (Journal of Human Rights, Culture and Legal System, 2022)
The Wali Nanggroe Aceh Institution is a unifying institution for the Acehnese people. Still, under the Aceh government law, this institution is not given enough space to carry out Aceh's duties and responsibilities. The results of this study are as follows: First, the authority of the Aceh Wali Nanggroe Institution is one of the things to unify the Acehnese people, but in fact, this authority is not included in the program budget of the Aceh Wali Nanggroe Institution because the budgetary control that manages it is the State Civil Apparatus assigned to the secretariat of the Aceh Wali Nanggroe Institution. Second, the word non-Aceh is no longer relevant because the Aceh Qanun on the Implementation of Population Administration has explained what is categorized as Acehnese. The perspectives of several ethnic groups fully support the existence of Wali Nanggroe Aceh Institution, but some people do not agree. Third, constitutionally the Wali Nanggroe Aceh Institution is protected by the constitution as part of the specialties and privileges of the Acehnese people.